Behavioral analysis of thermoelectric module under different configurations and temperature gradient - Ramizi Mohamed,; Azdiana Md. Yusop,; Azah Mohamed,; Nur Izzati Nordin, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study analyzes the behavior of the thermoelectric module (TEM) in a transient status which allows natural cooling condition. The analysis mainly aims to extract energy from the ordinary heat source and convert it into useful electrical power. Several TEM configurations which involve single TEM and multi stage TEM are manipulated within the system since the previous studies only focused on single TEM behavior only. For a complete TEM behavioral analysis results, the performance of multistage TEM must be taken into account as this type of configurations is usually used in highend TEM application to produce greater voltage value. A multistage TEM that is connected electrically in series and thermally in parallel produces a higher generated voltage value compared to a single TEM. TEM temperature gradients also are changed throughout the experiment to examine how this term affects the TEM behavior. The results show that the multistage TEM contributes the highest output voltage and it depends on the number of cascaded TEM. Furthermore, a higher temperature gradient contributes to more voltage generated by the TEM. TEM analysis with heatsink is proved to have larger temperature gradient to maintain the cold side of the TEM junction. Loading effect analysis shows that the TEM system can obtain 5 V of stable voltage when the load resistor connected to the system output is 200 Ω and above.